2011
DOI: 10.1371/journal.pone.0024294
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of BH3-Mimetic ABT-737 with the Alkylating Agent Temozolomide Induces Strong Synergistic Killing of Melanoma Cells Independent of p53

Abstract: Metastatic melanoma has poor prognosis and is refractory to most conventional chemotherapies. The alkylating agent temozolomide (TMZ) is commonly used in treating melanoma but has a disappointing response rate. Agents that can act cooperatively with TMZ and improve its efficacy are thus highly sought after. The BH3 mimetic ABT-737, which can induce apoptosis by targeting pro-survival Bcl-2 family members, has been found to enhance the efficacy of many conventional chemotherapeutic agents in multiple cancers. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
(36 reference statements)
3
39
0
Order By: Relevance
“…Hence, our treatment combination significantly enhanced efficacy compared to treatment with either agent alone, confirming positive data reported with the BH3-mimetic ABT-737 and various chemotherapies such as fotemustine [31], temozolomide [31], [32], melphalan [33], cytosine arabinoside [34], gemcitabine [35], actinomycine D [36], carboplatin [37], and others, or with Bcl-2 antisense and cyclophosphamide [38] or chlorambucil [39]. In the MM66 xenograft, this observation could be explained by the fact that fotemustine highly increased Bcl-2 expression that could be therefore more efficiently inhibited.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, our treatment combination significantly enhanced efficacy compared to treatment with either agent alone, confirming positive data reported with the BH3-mimetic ABT-737 and various chemotherapies such as fotemustine [31], temozolomide [31], [32], melphalan [33], cytosine arabinoside [34], gemcitabine [35], actinomycine D [36], carboplatin [37], and others, or with Bcl-2 antisense and cyclophosphamide [38] or chlorambucil [39]. In the MM66 xenograft, this observation could be explained by the fact that fotemustine highly increased Bcl-2 expression that could be therefore more efficiently inhibited.…”
Section: Discussionsupporting
confidence: 83%
“…However, primary human SCLC xenografts were less responsive, as were other SCLC lines in vitro (16). Recent studies have reported synergy between ABT-737 or its relative ABT-263 and cytotoxic drugs in a variety of tumor xenograft models (47,(49)(50)(51), including melanomas (52,53). The IC 50 values we observed for ABT-737 on NOXAoverexpressing melanoma cells in flat culture were comparable with those reported for ABT-737-sensitive SCLC and lymphoid malignancies (13).…”
Section: Discussionsupporting
confidence: 82%
“…If so, it does not represent an obstacle in principle. The MM200 cells tested may not be representative melanoma xenografts, as suggested by the responsiveness of A375 xenografts to ABT-737 plus temozolomide (52). In any case, development of more diffusible BH3 mimetics (56), which have improved oral bioavailability, charge balance, and metabolism properties, will likely obviate such problems.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Recent studies indicated that BH3-mimetics can be used to treat nonlymphoid cancers but mostly in combination with oestrogen antagonists, proteasome inhibitors, specific PI3K-mTOR inhibitors or chemotherapy. 24,[44][45][46][47][48][49] As previous findings from our laboratory demonstrated that E-cadherin-negative lobular breast cancer depends on p120-catenin-mediated activation of RhoA, Rock and subsequent actomyosin contraction, 26 we anticipate that dual inhibition of these pathways might be successful in E-cadherin-negative cancers that are not driven by oncogenic activation of GFR pathways. Although we do not yet know whether RhoA-Rock signals converge onto the GFR-AKT-FOXO axis in the regulation of anoikis resistance, the fact that FOXO expression had no effect on survival of B-RAF/KRAS-mutated MDA-MB-231 cells seems to be in line with this assumption.…”
Section: Discussionmentioning
confidence: 86%